Membangun Karakter Cinta Lingkungan Sejak Dini Melalui Pengolahan Sampah Menjadi Kerajian di SDN Suco 3 Kecamatan Mumbulsari Kabupaten Jember - Purnamasari, Ika; Ristiyana, Suci; Wahyu Saputra, Tri; Wijayanto, Yagus; Sholikhah, Ummi; Ratnasari, Tri (Universitas Mataram, 2024)
Humans who have strong character both individually and socially will form good morals and manners. The application of good character can be expressed in the form of loving the environment. One form of loving the environment is by processing waste into useful crafts. The service at SDN Suco 3 is carried out to implement students' environmental love character by instilling the importance of loving the environment, inviting students to get used to sorting waste and equipping students with the skills to process waste into attractive wall decoration crafts. This activity was well received by students and teachers and had a positive impact on creating a more enjoyable learning atmosphere for students.